Building R&D leadership and credibility - Uttal, Bro (Research management (Now: research technology management))
Bro Uttal, Alan Kantrow, Lawrence H. Linden, and B. Susan Stock suggest how to close the gap between the leadership a company needs and the leadership it often gets from its technical heads.